Combined Relay Selection and Cooperative Beamforming for Physical Layer Security - Kim, Junsu; Ikhlef, Aissa; Schober, Robert (Journal of Communications and Networks, 2012)
In this paper, we propose combined relay selection and cooperative beamforming schemes for physical layer security. Generally, high operational complexity is required for cooperative beamforming with multiple relays because of the required information exchange and synchronization among the relays. On the other hand, while it is desirable to reduce the number of relays participating in cooperative beamforming because of the associated complexity problem, doing so may degrade the coding gain of cooperative beamforming. Hence, we propose combined relay selection and cooperative beamforming schemes, where only two of the available relays are selected for beamforming and data transmission. The proposed schemes introduce a selection gain which partially compensates for the decrease in coding gain due to limiting the number of participating relays to two. Both the cases where full and only partial channel state information are available for relay selection and cooperative beamforming are considered. Analytical and simulation results for the proposed schemes show improved secrecy capacities compared to existing physical layer security schemes employing cooperative relays. © 2012 KICS
CRIS-Team Scopus Importer:2020-02-03
Keywords: Cooperative beamforming; optimal beamforming; physical layer security; relay selection